KONSEP DAN IMPLEMENTASI AL-‘ÂMM DAN AL-KHÂSH DALAM PERISTIWA HUKUM KONTEMPORER - Sofian Al Hakim (Asy-Syari'ah, 2015)
Al-Quran is a way of life for Muslims, then of the Koran becomes important to study because it is considered as the practice of most of the renowned and as a source of Islamic law (mashâdîr al-Ahkâm) in resolving a problem. The device to be able to issue a law from the source (al-Quran) is called ijtihad. One of the main tasks of a mujtahid must understand the text (Nash), which is better to understand the meaning of a lafaz, area, object, and how the appointment lafaz on the meaning and the type and degree of his dilalah. Experts ushûl fiqh divide this theme into two parts, namely the appointment (dilâlah) text on a meaning and appointment (dilâlah) directly on the legal texts of syara‘. Appointment (dilâlah) text on a meaning it includes the study ‘âmm and khâsh. Therefore, this paper will be focused on the concept and implementation of the 'Amm and khâsh in legal events in the present, so that there is clarity about the legal position that is not explicitly described in the al-Quran and al-Sunnah.